2015
DOI: 10.1016/j.forpol.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

CO2 emissions and economic impacts of using logging residues and mill residues in Maniwa Japan

Abstract: ✜ Abstract:In the face of increasing demand for woody biomass, mill residues continue being used more frequently than logging residues in Japan because of their relative ease of use.The Japanese government set a target ratio of logging residue use to 30 percent by 2030 compared with less than 1 percent in 2009. This study examined GHG emissions and the economic effects of logging and mill residues, which are employed as raw materials for various purposes in Maniwa, Japan.In 2012, 23,710 tonnes of woody biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The production of bioenergy from logging residues could lead to a variety of cobenefits. Several studies have reported that the largest impact of using logging residues for bioenergy production is the observed improvement in environmental emissions (Gan and Smith 2006;Sathre and Gustavsson 2011;Kukrety et al 2015;Moon et al 2015;Repo et al 2015). Another important aspect is the reduction in fossil fuel dependency for overall energy production (Kukrety et al 2015;Moon et al 2015;Rothe et al 2015).…”
Section: Environmental Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of bioenergy from logging residues could lead to a variety of cobenefits. Several studies have reported that the largest impact of using logging residues for bioenergy production is the observed improvement in environmental emissions (Gan and Smith 2006;Sathre and Gustavsson 2011;Kukrety et al 2015;Moon et al 2015;Repo et al 2015). Another important aspect is the reduction in fossil fuel dependency for overall energy production (Kukrety et al 2015;Moon et al 2015;Rothe et al 2015).…”
Section: Environmental Aspectsmentioning
confidence: 99%
“…Several studies have reported that the largest impact of using logging residues for bioenergy production is the observed improvement in environmental emissions (Gan and Smith 2006;Sathre and Gustavsson 2011;Kukrety et al 2015;Moon et al 2015;Repo et al 2015). Another important aspect is the reduction in fossil fuel dependency for overall energy production (Kukrety et al 2015;Moon et al 2015;Rothe et al 2015). Apart from lessening the overall environmental impact of electrical energy generation and promoting energy security, the utilization of logging residue for bioenergy production will create job opportunities (Kukrety et al 2015).…”
Section: Environmental Aspectsmentioning
confidence: 99%
“…Harvesting residues are the biomass left on fields after wood harvesting (tops, branches, and little non-marketable trunks) [1]. On average, 10% to 15% of this biomass is left on site as forest residues following harvesting operations [2] because it is expensive to harvest and transport and there are few markets for this wood material.…”
Section: Introductionmentioning
confidence: 99%